Empowering women for health security in India: a One Health cascade training model for strengthening biosecurity through women veterinarians and farmers - Ravina Tadvi; Jessica Taaffe; Ashley Tseng; Shrankhala Mishra; Pratiksha Pundir; Shailee Patil; Sandul Yasobant; Deepak Saxena; Falgunee K. Parekh (Frontiers in Public Health, 2026)
Introduction Zoonotic diseases remain a significant public health threat in India, where human–animal interactions are frequent due to its dense population and distinct agricultural economy that lends itself to an increased risk of zoonotic spillover of high-consequence pathogens. Despite policy initiatives promoting One Health approaches, barriers like limited awareness and inadequate biosecurity practices persist. Women farmers play crucial yet under-recognized roles in livestock management but have limited access to training on best biosecurity practices due to limited engagement with male veterinary health professionals, who primarily conduct field visits in India. Women veterinary health professionals (WVHPs) can operationally engage better with WFs but similarly face barriers to entry for fieldwork positions and have limited access to training for professional growth. Methods To address this gap, we designed and implemented an innovative cascade-training model with the goal of strengthening detection and prevention of high-consequence pathogens by linking WVHPs and WFs. We employed a cascade-training model beginning with training of WVHPs on biosafety, biosecurity, One Health, and community engagement and equipping them with the tools and skills to train WFs. These trained WVHPs implemented local training sessions for WFs using interactive tools like case studies and games. Acquired knowledge metrics were assessed through pre- and post-training assessments and focus group discussions (FGDs). Results We trained 38 WVHPs, and knowledge scores improved from 10.6 ± 2.49 to 11.3 ± 2.47 when given the same questions in pre- and post-assessments. The FGDs demonstrated WVHPs’ understanding of WF knowledge and issues faced. Three overarching themes emerged regarding WF capacity building: knowledge gaps and high-risk practices, structural and sociocultural barriers, and pathways for effective community engagement/knowledge transfer. Of the 152 WFs trained, 79.9% could identify clinical signs of animal sickness, and 85.9% recognized integrated prevention practices. However, gaps in zoonotic disease awareness and sanitation practices were evident. Conclusion The cascade-training model demonstrated that engaging women professionals as both practitioners and trainers can advance community-level biosecurity practices and disease detection. Embedding such women-centred approaches within national One Health strategies can strengthen India’s biosecurity systems and contribute to global health security goals.